2016
DOI: 10.1007/s00464-016-5304-0
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal mucosal integrity improves after laparoscopic antireflux surgery in children with gastroesophageal reflux disease

Abstract: BackgroundEsophageal intraluminal baseline impedance reflects the conductivity of the esophageal mucosa and may be an instrument for in vivo evaluation of mucosal integrity in children with gastroesophageal reflux disease (GERD). Laparoscopic antireflux surgery (LARS) is a well-established treatment option for children with proton pump inhibitory (PPI) therapy resistant GERD. The effect of LARS in children on baseline impedance has not been studied in detail. The aim of this study was to evaluate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Going in line with this notion, a recent study found that elimination of the reflux after effective fundoplication is more effective to restore the electrical resistance of the esophagus. 11 Taken together, the above studies show that electrical resistance serves as a sensitive measure to monitor the integrity of the esophageal epithelium before and after medical or surgical therapy of GERD and BE. [7][8][9][10][11] Conceptually, GERD results from a refluxinduced orchestration of an inflammatory response, involving epithelial, nerve, inflammatory, and muscle cells within the esophageal mucosa 4-6 ( Fig.…”
Section: Reflux and Mucosal Integritymentioning
confidence: 74%
See 2 more Smart Citations
“…Going in line with this notion, a recent study found that elimination of the reflux after effective fundoplication is more effective to restore the electrical resistance of the esophagus. 11 Taken together, the above studies show that electrical resistance serves as a sensitive measure to monitor the integrity of the esophageal epithelium before and after medical or surgical therapy of GERD and BE. [7][8][9][10][11] Conceptually, GERD results from a refluxinduced orchestration of an inflammatory response, involving epithelial, nerve, inflammatory, and muscle cells within the esophageal mucosa 4-6 ( Fig.…”
Section: Reflux and Mucosal Integritymentioning
confidence: 74%
“…Since patients receive high‐dose PPI therapy after RFA, these resistance differences between normal and neo‐squamous epithelium are suggested to be attributed to the lack of elimination of the reflux per se. Going in line with this notion, a recent study found that elimination of the reflux after effective fundoplication is more effective to restore the electrical resistance of the esophagus …”
Section: Reflux and Mucosal Integritymentioning
confidence: 78%
See 1 more Smart Citation
“…Authors Moritz A. F., Rinsma N. F., and Ernest L. V. studied the effect of laparoscopic antireflux surgery on the initial impedance as a reflection of the integrity of the mucosa in 25 children with gastroesophageal reflux disease and concluded that surgical antireflux protection performed laparoscopically reduces the time of acid exposure from 8.5% (6.0%–16.2%) to 0.8% (0.2%–2.8%), P < 0.001, respectively, increases the distal resistance, resulting in restoration of the base impedance, reduction of reflux symptoms, and restoration of the integrity of the esophageal mucosa. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic antireflux surgery significantly increased baseline impedance likely reflecting recovery of mucosal integrity [10]. Duration of stay is an important clue in our discussion that we touched a little on discussingat the above problem of laparoscopic cost operators.…”
Section: Discussionmentioning
confidence: 99%